2004
DOI: 10.17159/2078-516x/2004/v16i2a183
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in acute-phase reactants (CRP, rheumatoid factor, complement, Factor B, and immune complexes) following an ultramarathon

Abstract: Objectives. The human body initiates an acute phase response (APR) in response to a wide range of homeostatic disturbances. This complex series of reactions serves to activate repair processes and prevent ongoing tissue damage. An important aspect of the APR is the de novo synthesis of acute phase proteins (APP), many of which have not been thoroughly investigated. Main outcome measures.Alterations in CRP (C-reactive protein), C1est, C3, C4, C6, rheumatoid factor (RF) and Factor B were determined before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Mashiko et al [22] reported a similar post-game observation in rugby players. In contrast to our findings for the Beep test, the levels of C3 and C4 after short-term maximal exercise rapidly returned to baseline values [40,54], but they stayed slightly lowered after an ultramarathon [55]. When analyzing the runners, Smith et al reported that short-term aerobic exercise triggers the activation of C3 and C4 complement components and subsequent increase in C3a and C4a [56].…”
Section: Discussioncontrasting
confidence: 99%
“…Mashiko et al [22] reported a similar post-game observation in rugby players. In contrast to our findings for the Beep test, the levels of C3 and C4 after short-term maximal exercise rapidly returned to baseline values [40,54], but they stayed slightly lowered after an ultramarathon [55]. When analyzing the runners, Smith et al reported that short-term aerobic exercise triggers the activation of C3 and C4 complement components and subsequent increase in C3a and C4a [56].…”
Section: Discussioncontrasting
confidence: 99%
“…The acute phase response (APR) to muscle/tissue damage, specifically the activation of complement components C3, C4 and C5 fragments, may be a possible mechanism for activating eosinophils. 13 Submitted data from the present study have shown that the same ultramarathon caused an APR and an increase in complement, 38 and this may have played a role in the non-allergic activation of eosinophils.…”
Section: Discussionsupporting
confidence: 50%
“…25,40,45 Although there is general consensus regarding the induction of an acute-phase inflammatory response following strenuous, unaccustomed or prolonged bouts of exercise, there is some degree of uncertainty surrounding the precise stimuli responsible for this response. The majority of authors have attributed the rise in inflammatory markers following physical activity to muscle damage.…”
Section: Inflammation and Exercisementioning
confidence: 99%
“…Increases in CRP have been observed following acute strenuous, prolonged bouts of running, 40 triathlon, 16,47 bench stepping 12 and anaerobic exercise. 26 Since eccentrically based exercise is more commonly associated with muscle damage, and CRP serves to bind damaged cells, it seems reasonable to assume that this type of activity would be associated with pronounced elevations in CRP.…”
Section: Effects Of Acute Exercise On Crpmentioning
confidence: 99%